2002
DOI: 10.1063/1.1493180
|View full text |Cite
|
Sign up to set email alerts
|

Rovibrational structure of the Ar–CO complex based on a novel three-dimensional ab initio potential

Abstract: The first three-dimensional ab initio intermolecular potential energy surface of the Ar-CO van der Waals complex is calculated using the coupled cluster singles and doubles including connected triples model and the augmented correlation-consistent polarized valence quadruple zeta ͑aug-cc-pVQZ͒ basis set extended with a (3s3 p2d1 f 1g) set of midbond functions. The three-dimensional surface is averaged over the three lowest vibrational states of CO. Rovibrational energies are calculated up to 50 cm Ϫ1 above the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 56 publications
1
34
0
Order By: Relevance
“…Examples of this approach are provided by the development of 3D PESs for the H 2 -Ar interaction by Bissonnette et al 7 and for the H 2 − Kr interaction by Wei et al; 8 in both cases, the parameters in the XC PESs were obtained by fitting to selected IR spectroscopic data. The 3D XC͑0͒ PES for Ne-CO and its modifications discussed briefly here add to the family 43,69,70 currently available for noble gas-CO dimers. It is worth emphasizing here that the relatively small differences between a 2D rigid-rotor PES, such as the XC͑fit͒ r=r e PES, and the vibrationally averaged XC͑fit͒ v CO =0 and XC v CO =1 PESs are important both in principle and in practice, especially for mid-IR spectroscopic transitions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of this approach are provided by the development of 3D PESs for the H 2 -Ar interaction by Bissonnette et al 7 and for the H 2 − Kr interaction by Wei et al; 8 in both cases, the parameters in the XC PESs were obtained by fitting to selected IR spectroscopic data. The 3D XC͑0͒ PES for Ne-CO and its modifications discussed briefly here add to the family 43,69,70 currently available for noble gas-CO dimers. It is worth emphasizing here that the relatively small differences between a 2D rigid-rotor PES, such as the XC͑fit͒ r=r e PES, and the vibrationally averaged XC͑fit͒ v CO =0 and XC v CO =1 PESs are important both in principle and in practice, especially for mid-IR spectroscopic transitions.…”
Section: Discussionmentioning
confidence: 99%
“…Obvious exceptions are the calculation of vibrational relaxation times [40][41][42] and IR vibrational transition frequencies. 7,8,43 The variant of the XC model to be employed here is a diatom bond-length-dependent extension 7,8 of the 2D individually damped XC model, originally developed to describe closed-shell atom-atom interactions ͑see Refs. 1-6 and references therein͒ and successfully extended to Rg-diatom interactions.…”
Section: The Ne-co Exchange-coulomb Model Potential Surfacementioning
confidence: 99%
“…Some previous works 11,14 showed that the vibrationally adiabatic potential provides a good explanation for the experiment results. The vibrationally averaged Ne-CO potential can be expressed as…”
Section: B Fitting Proceduresmentioning
confidence: 99%
“…On the theoretical [11][12][13][14][15][16] side, a lot of attentions were attracted on the Rg-CO complexes. For instance, in 2005, Peterson and McBane 11 constructed the three-dimensional PES of the He-CO complex.…”
Section: Introductionmentioning
confidence: 99%
“…1 and the isotropic potential is shown in Panel (e). The CO-Ar potential 33 (Panel (b) of Fig. 1) is the same as used before in our study 25 for isolated CO, with the bond length fixed to r CO = 1.1324 Å in the potential simulation.…”
Section: Rotational Raman Spectrum Of Hmentioning
confidence: 99%